A Preliminary Survey in Improving Learning Space Facilities and Environment in "Tunas Bangsa" Early Childhood Education - Hani Zulfia Zahro'; Tutut Nani Prihatmi; Ghoustanjiwani Adi Putra (ESE International Journal (Environmental Science and Engineering), 2021)
With a population of 11,200 people, Harjokuncaran village still has a reasonably high poverty rate accompanied by a low majority of education levels. This condition can be seen from the educational facilities and environment, especially in early childhood education institutions. One example is in PAUD Tunas Bangsa 02 as the study object in this research. Data collection was carried out by field observation and direct interviews. The collected qualitative data are sorted by content analysis, displayed using the data display method and presented in data grouping. This qualitative research stage was only limited to the Preliminary Survey. At this preliminary stage, the research will only focus on obtaining data, include regional conditions, spatial, and physical and social characteristics data. These three types of data will be used as initial data in determining the next research process in the future.